Fast-Suppressor Screening for New Components in Protein Trafficking, Organelle Biogenesis and Silencing Pathway in Arabidopsis thaliana Using DEX-Inducible FREE1-RNAi Plants. Issue 6 (20th June 2015) - Zhao, Qiong; Gao, Caiji; Lee, PoShing; Liu, Lin; Li, Shaofang; Hu, Tangjin; Shen, Jinbo; Pan, Shuying; Ye, Hao; Chen, Yunru; Cao, Wenhan; Cui, Yong; et al.
Abstract Membrane trafficking is essential for plant growth and responses to external signals. The plant unique FYVE domain-containing protein FREE1 is a component of the ESCRT complex (endosomal sorting complex required for transport). FREE1 plays multiple roles in regulating protein trafficking and organelle biogenesis including the formation of intraluminal vesicles of multivesicular body (MVB), vacuolar protein transport and vacuole biogenesis, and autophagic degradation. FREE1 knockout plants show defective MVB formation, abnormal vacuolar transport, fragmented vacuoles, accumulated autophagosomes, and seedling lethality. To further uncover the underlying mechanisms of FREE1 function in plants, we performed a forward genetic screen for mutants that suppressed the seedling lethal phenotype of FREE1-RNAi transgenic plants. The obtained mutants are termed as suppressors of free1 (sof). To date, 229 putative sof mutants have been identified. Barely detecting of FREE1 protein with M3 plants further identified 84 FREE1-related suppressors. Also 145 mutants showing no reduction of FREE1 protein were termed as RNAi-related mutants. Through next-generation sequencing (NGS) of bulked DNA from F2 mapping population of two RNAi-related sof mutants, FREE1-RNAi T-DNA inserted on chromosome 1 was identified and the causal mutation of putative sof mutant is being identified similarly. These FREE1- and RNAi-related sof mutants will be useful tools and resources for illustrating the underlying mechanisms of FREE1 function in intracellular trafficking and organelle biogenesis, as well as for uncovering the new components involved in the regulation of silencing pathways in plants.